Emergency Orthopedics A Manual on Acute Conditions of the Locomotor System - Sölveborn, Sven-Anders (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Emergency Orthopedics is a practical, up-to-date, and comprehensive manual on the diagnosis and treatment of emergency injuries and disorders of the locomotor system. Its problem-based structure, with each chapter addressing a particular symptom, is designed to allow the reader to rapidly locate hands-on advice relevant to a wide range of circumstances. For each symptom, facts and findings that will assist in diagnosis are highlighted. Possible diagnoses are suggested according to the ICD-10 code, and the proposed treatment recommendations consider both short- and long-term aspects. In addition, important issues such as osteoporosis, joint injection techniques, and burn injuries are considered in separate chapters. The text is supported by exceptionally instructive illustrations, e.g., of examination techniques and reduction maneuvers.   The book is written with a wisdom reflecting the author's extensive practical experience in emergency rooms as well as in sports medicine, research, and education. It will be a treasure trove of information for all who work in the emergency room and also very useful for general practitioners, physiotherapists, and chiropractors.